ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI WIRAUSAHA ERA REVOLUSI INDUSTRI 4.0 MAHASISWA IST AKPRIND YOGYAKARTA - Aji Pranoto; Eka Sulistyaningsih; Nurul Dzakiya (Jurnal Pendidikan Vokasi Otomotif, 2020)
Abstract - This study is to analyze the influence of entrepreneurial motivation factors in the era of 4.0 including family background, entrepreneurial education training, courage to take risks, and the desire to work independently of the students of the AKPRIND Yogyakarta Institute of Science Technology. This type of research is ex-post facto. The population of all students taking entrepreneurship courses in the odd semester of 2020/2021 is 61 students. Data collection using a questionnaire. The validity test used the item score correlation with the total score, the reliability used Cronbach alpha, the data analysis technique used descriptive analysis and SEM. Data processing using the help of a computer program Lisrel. The results of this study indicate that there is a direct influence of 1) family background (X1) on the entrepreneurial motivation variable (Y) of 0.33 and the value of t = 6.33. 2) entrepreneurship education and training (X2) on the entrepreneurial motivation variable (Y) of 5.28 and the value of t = 5.38. 3) courage to take risks (X3) on the entrepreneurial motivation variable (Y) of 0.24 and the value of t = 4.87. 4) the desire to work independently (X4) on the entrepreneurial motivation variable (Y) of 5.22. While the indirect effect of variable 1) family background (X1) on the courage to take risks (X3) is 0.26 and the value of t = 4.28. 2) entrepreneurship education and training (X2) on the risk-taking courage variable (X3) of 0.14 and the value of t = 2.27. 3) family background (X1) on the variable desire to work independently (X4) of 0.27 and the value of t = 4.07. 4) entrepreneurship education and training (X2) on the variable desire to work independently (X4) of 0.13 and the value of t = 1.72.